Addressing relationship quality of people with dementia and their family carers: which profiles require most support? - Marques, Maria J.; Woods, Bob; Jelley, Hannah; Kerpershoek, Liselot; Hopper, Louise; Irving, Kate; Bieber, Anja; Stephan, Astrid; Sköldunger, Anders; Sjölund, Britt‐Marie; Selbaek, Geir; Røsvik, Janne; et al. (Frontiers in Psychiatry, 2024)
Objective: The quality of the relationship between persons with dementia and family carers influences health and quality of life outcomes. Little is known regarding those at higher risk of experiencing a decline in relationship quality, who could potentially benefit the most from interventions. We aimed to identify these risk profiles and explore the underlying factors. Methods: We applied a latent profile analysis to relationship quality data from a 1-year follow-up of 350 dyads of persons with dementia and their informal carers from the Actifcare cohort in eight European countries. Assessments included sociodemographic, clinical, functional, psychosocial and quality of life measures. Relationship quality was assessed with the Positive Affect Index. A discriminant analysis explored factors influencing the risk profiles. Results: There were two relationship quality profiles among persons with dementia (gradually decreasing, 74.0%; low but improving, 24.6%) and two among carers (steadily poor, 57.7%; consistently positive, 42.3%). The ‘gradually decreasing’ profile (persons with dementia) was related to their levels of dependence and unmet needs, along with carers’ social distress and negative feelings, lower baseline RQ and sense of coherence. The ‘steadily poor’ profile (carers) was influenced by their social distress and negative feelings, lower sense of coherence and perceived social support. These two predominant profiles showed significant decreases in quality-of-life over one year. Conclusions: Specific profiles of persons with dementia and their carers are at risk of worse relationship quality trajectories. By considering modifiable related factors (e.g., carers’ stress), our findings can help develop tailored, effective interventions.